Development and validation of a nomogram model for predicting residue of partially cystic thyroid nodules after ultrasound-guided ethanol and thermal ablation - Li, Di; Zhang, Xiaoer; Zhang, Yutong; Huang, Tongyi; Zhang, Rui; Zhou, Wenwen; Xie, Xiaoyan; Xu, Ming (Frontiers in Endocrinology, 2023)
Objectives: To develop and validate a nomogram model for predicting residue of partially cystic thyroid nodules (PCTNs) after ethanol and thermal ablation. Materials and Methods: From July 2015 to August 2022, a total of 97 patients (age 40.78±12.61 years) with 107 treated benign PCTNs receiving ethanol and thermal ablation were enrolled. Pre-ablative laboratory test results and the ultrasound (US) and contrast-enhanced ultrasound (CEUS) features of lesions were collected. They were categorized into non-residue group and residue group according to the CEUS examination assessment after ablation. Univariate and multivariate logistic regression analysis were adopted to build a nomogram. The nomogram was validated by internal stratified fivefold cross-validation. The calibration, discrimination and clinical utility of the nomogram were investigated to assess the performance of the model. Results: Residue was reported in 30 out of 107nodules (28.0%). Multivariate logistic regression analysis revealed initial volume (OR=1.12, 95%CI 1.06-1.19) and presence of septum (OR=3.19, 95%CI 1.09-9.36) were predictors of residue of PCTNs. The nomogram developed by the above factors showed good calibration and discrimination. The area under the curve (AUC), sensitivity and specificity of this model were 0.832, 86.7% and 68.8%, respectively. When applied to internal validation, the model revealed good generalizability with stratified fivefold cross-validation in the cohort (mean AUC = 0.821). Conclusions: The nomogram model has good performance for predicting the residue of PCTNs undergoing ethanol and thermal ablation. This could play a role in the decision of treatment and follow-up in clinical practice.